Identification of Microplastic in Water, Sediment, and Fish in Lematang River, Lahat - Rasyiqa Fauzia; Yuanita Windusari; Afifah Muntiah (GLOBAL HEALTH SCIENCE GROUP, 2024)
Microplastic is formed from plastic waste that enters water and decomposes over a certain period of time through chemical, physical, and biology processes that then change the plastic waste into plastic particles with micro sizing that is known as microplastics. This research is quantitative descriptive research that aims to determine the morphology, size, and color of microplastics on the samples that were collected from Lematang River then particles that are already trapped on the membrane filters are then observed under a microscope. Identification of microplastic forms in samples at the Lematang River using a trinocular microscope. The forms of microplastics found in the samples are categorized into 5 forms, which are film, fiber, foam, fragment, and pellet.